Young Adult Street Vendors and Adverse Respiratory Health Outcomes in Bangkok, Thailand - Saisattha Noomnual; Derek G. Shendell (Elsevier, 2017)
Air pollutants of concern include traffic-related air pollution, including particulate matter in respirable coarse and fine size fractions. There are no critical studies to date into associations between knowledge, awareness, and attitudes in using proper respiratory masks and prevalence of respiratory symptoms among urban street vendors in Thailand. In this study, we estimated adverse respiratory health outcomes among street vendors, in particular young adults, in Bangkok, Thailand, using a self-report questionnaire. Street vendors, who were not currently smoking and not having known diagnosed respiratory diseases, were recruited. They were selected from selected roadsides at Chong Nonsi, Bangkok. Participants (n=30) reported having lower respiratory (50%), upper respiratory (37%), and other symptoms (70%). Also, 53% of participants had never used respiratory personal protective equipment (PPE: masks). Among those using PPE, all used masks not proper for particulate matter. Results suggested knowledge, awareness, and attitudes concerning proper PPE use needs to be increased among street vendors in Bangkok, Thailand. Keywords: respiratory protective masks, respiratory symptoms, street vendors, Thailand, urban environment